Bendamustine with rituximab, etoposide and carboplatin (T(R)EC) in relapsed or refractory aggressive lymphoma: a prospective multicentre phase 1/2 clinical trial. (14th September 2018) - Budde, Lihua E.; Wu, David; Martin, Daniel B.; Philip, Mary; Shustov, Andrei R.; Smith, Stephen D.; Gooley, Ted A.; Chen, Tara L.; Libby, Edward N.; Chen, Eric Y.; Kojouri, Kiarash; Langerak, Alan; et al.
Summary: We sought to develop a safe and effective outpatient salvage regimen by replacing ifosfamide within the (R)ICE (rituximab, ifosfomide, carboplatin, etoposide) regimen with bendamustine (T(R)EC) via a multicentre phase I/II study for patients with relapsed or refractory diffuse large B cell lymphoma (DLBCL) and classic Hodgkin lymphoma (HL). Therapy consisted of 60–120 mg/m 2 per day bendamustine on days 1 and 2 in combination with carboplatin, etoposide and rituximab (only for CD20 + lymphoma) used in the (R)ICE regimen for up to 2 cycles. The objectives were to define a maximally tolerated dose (MTD) of bendamustine, determine safety and toxicity, assess efficacy, and evaluate impact on stem cell collection. Forty‐eight patients were treated of which 71% had refractory disease. No dose‐limiting toxicities were observed. The recommended phase II dose of bendamustine was 120 mg/m 2 per day on days 1 and 2. Response rates were 85% (70% complete response, CR) in HL, and 65% (40% CR) in DLBCL. Stem cell collection was successful in 30 of 32 patients. The most common non‐haematological toxicities ≥grade 3 were febrile neutropenia (8%) and dehydration (8%). The T(R)EC regimen safely yields high response rates, successfully mobilizes peripheral blood stem cells and compares favourably to RICE, offering an effective outpatient treatment option for patients with relapsed or refractory DLBCL and HL.